Prevention and Control Strategies for Coronavirus Disease-2019 in a Tertiary Hospital in the Middle East of China - Kong Q; Yan L (Dove Medical Press, 2020)
Qingfang Kong, Li Yan Department of Infection Prevention and Control, Zhongda Hospital Affiliated to Southeast University, Nanjing 210009, People’s Republic of ChinaCorrespondence: Qingfang KongZhongda Hospital Affiliated to Southeast University, No. 87 Dingjiaqiao, Nanjing, People’s Republic of ChinaEmail njkqf@163.comBackground: Coronavirus disease-2019 (COVID-19) is a new infectious disease. The COVID-19 outbreak has quickly spread globally and now is having remarkable effects on public health and national economies.Purpose: Effective measures for prevention and control of nosocomial infection are urgently needed to control COVID-19 infection among medical staff.Methods: Herein, we described COVID-19 prevention and control strategies that have been implemented in a tertiary hospital in the middle east of China. Hospital layout was adjusted to prevent and control transmission. Other procedures were then implemented to prevent the spread of the virus, including specialized training and evaluation of medical staff, pre-testing and triage, measures to promote early identification of patients, environmental cleaning and disinfection, new medical waste processing procedures, new patient management procedures, timely disinfection of potential sources of nosocomial infection, and strict protective measures.Results: Since the new measures were implemented, to date there have only been three new confirmed cases of COVID-19 infection, no cases of medical staff infection, and no COVID-19-related deaths at the hospital.Conclusion: The current report provides a protocol that could be implemented in medical departments in similar cities worldwide.Keywords: COVID-19, health-associated infection, infection management, SARS-CoV-2